2011
DOI: 10.1002/jip.142
|View full text |Cite
|
Sign up to set email alerts
|

How Effective is the Enhanced Cognitive Interview when Aiding Recall Retrieval of Older Adults including Memory for Conversation?

Abstract: The percentage of older adults in the general population is growing. As a result, older adults are coming more frequently into contact with the Criminal Justice System as witnesses to and victims of crime. Older adults are also over-represented in crimes where conversation detail is of particular importance to an investigation (e.g. distraction burglary). The present study therefore examined the efficacy of cognitive interview (CI) compared with structured interview in improving the recall of an event by older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
2
31
0
1
Order By: Relevance
“…The observed increased recall of conversation gist information by both adults with and without ID when interviewed using the CI is consistent with and builds upon the works of Campos & Alonso‐Quecuty () and Prescott et al . (), who both used a sample which did not included adults with ID. This is important as conversation detail may be the only type of information that can lead to the successful prosecution of non‐physical crimes, such as verbal abuse (Campos & Alonso‐Quecuty ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed increased recall of conversation gist information by both adults with and without ID when interviewed using the CI is consistent with and builds upon the works of Campos & Alonso‐Quecuty () and Prescott et al . (), who both used a sample which did not included adults with ID. This is important as conversation detail may be the only type of information that can lead to the successful prosecution of non‐physical crimes, such as verbal abuse (Campos & Alonso‐Quecuty ).…”
Section: Discussionmentioning
confidence: 99%
“…The CI also includes techniques such as transferring control to the participant by telling them that they are the chief expert about their experience, which lowers perceived expectations that the participant is undergoing a test where the interviewer knows the answers and the interviewee does not, as well as minimizing the tendency to interrupt the participant and asking mainly open-ended questions to support free recall (Memon et al, 2010). Several previous studies using different age groups have shown that the CI increases the amount of accurate information received in both older and young adults (Dornburg & McDaniel, 2006; Holliday et al, 2012; Prescott, Milne, & Clark, 2011; Wright & Holliday, 2007), although some studies have failed to find beneficial effects in either age group (e.g., McMahon, 2000; for discussion, see Holliday et al, 2012). …”
Section: The Present Studymentioning
confidence: 99%
“…to report somewhat uncertain information. ECI research (Dando & Milne, 2010;Prescott, Milne, & Clark, 2011) usually disregards such expressions in the coding and analysis. Thus, 'I think the robber had a gun' would (for example) simply be coded as 'the robber had a gun'.…”
Section: Developed the Cognitive Interview (Ci)mentioning
confidence: 99%
“…Also noted was the phase within the interview in which an item of information was recalled. If an item of information (correct or not) was repeated during the same, or a subsequent phase, that information was scored only the first time it was mentioned (Prescott et al, 2011). We classified items of information as either 'certainties' or 'uncertainties'.…”
Section: Different Internal Perspective In Order To Try To Remember Nmentioning
confidence: 99%
See 1 more Smart Citation